Benchmarking w ocenie efektywności krajowych spółek dystrybucyjnych energii elektrycznej - Nazarko, Joanicjusz; Chrabołowska, Joanna (Application Benchmarking Techniques to Efficiency Assesing of Polish Distribution Utilities, 2005)
The paper presents a overview of benchmarking techniques applied to electricity distribution utilities. An benchmarking study of 33 Polish electricity distribution utilities is presented to illustrate the methodological and data issues. The study examines the effect of the choice of benchmarking methods using DEA and SFA models.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 38-47